Nonlocal Parabolic Problem with Degeneration - Isaryuk, I. M.; Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the problem for a second-order linear parabolic equation with nonlocal integral condition in the time variable and power singularities in the coefficients of any order with respect to the time and space variables. By using the maximum principle and a priori estimates, we establish the existence and uniqueness of the solution of this problem in Hölder spaces with power weights.